Enhancing the Value of Blue Crab Chili Paste Products by the Local Fisherwomen Group in Khon Klan Subdistrict, Satun Province, Thailand - Wunsaeng, Thanapong; Seamhan, Porntip; Plongoon, Kanjana; Kraisanti , Kanida; Kasawapat, Supaluk; Thongchim, Pitoon; Sakunchannarong , Nisachon; Kongpim, Thaksornthan (Area Based Development Research Journal, 2024)
A group of local female fishermen from the Khon Khlan subdistrict in Satun province, Thailand has been producing and selling Blue Crab Chili Paste under the Rim Lay Shop brand. However, they faced several challenges, including product and packaging issues, setting prices that did not align with consumer needs, and a lack of diversified marketing channels, all of which resulted in low income and profit per unit. To address these problems, this research focused on enhancing the Blue Crab Chili Paste product to add value through the product development and group capacity building processes. In the product development process, the existing production process was studied and the recipe was adjusted to improve the texture. The packaging was upgraded from transparent plastic and glass bottles with screw caps to plastic pots using automated sealing technology. Additionally, a new brand identity, "Rim Lay," was developed to reflect the local community's natural, cultural, and religious identity. New product labels were designed, and a new pricing strategy was implemented. Consumer acceptance of the improved product and packaging was tested, along with production and distribution circuits. In the group capacity building, training workshops enhance the group’s knowledge of product branding, label design, brand image development, and distribution channels, both online and offline. The tourism management was also integrated into the project, encouraging community participation and feedback. The results of these development efforts were highly positive. The improved recipe and packaging, along with the new "Rim Lay" branding, were well-received, with 94% of 100 consumers expressing acceptance of the Blue Crab Chili Paste and giving it an overall appreciation score of 4.05 out of 5. This led to a 50% increase in sales and a 2.5 times increase in monthly income. The participatory learning approach and networking efforts empowered the group of local female fishermen to innovate further, adding new marketing channels to support tourism. As a result, the group has officially registered its business as the Rim Lay Khon Khlan Community Enterprise, producing Blue Crab Chili Paste as a community product that meets quality standards. The product is now positioned as a tourism product for the Khon Khlan subdistrict, contributing to the creation of a sustainable circular economy for the community.